THE ROLE OF PRODUCT QUALITY AND PRICE IN IMPROVING BROILER FEED BUYING DECISIONS IN PT. WONOKOYO JAYA KUSUMA, CIKANDE SUBSUBDISTRICT, SERANG REGENCY - Abdul Aziz; Fatari Fatari (Yayasan Education and Social Center, 2021)
The buying decision is a step where a person determines an option to buy the product he likes with factors. This study analyses the role of product quality and Price in improving broiler feed buying decisions in PT. Wonokoyo Jaya Kusuma, Cikande Subdistrict, Serang Regency. The research method used is a survey method with a quantitative approach. The results of the H1 test, the t-count value (2,671 ≥ 1.683), then H1 is accepted and H0 is rejected. This proves an effect between Product Quality (X1) on Buying Decisions (Y). H2, the value of t arithmetic (2,060 ≥ 1.68), then H2 is accepted and H0 is rejected. This proves that there is an effect between Price (X2) on Buying Decisions (Y). In the F test, the calculated F value (4,765) ≥ F table (3,16), then H0 is rejected, so it can be concluded that together there is an effect between the variables Product Quality (X1) and Price (X2) on Buying Decisions (Y) in PT. Wonokoyo Jaya Kusuma. The coefficient of determination (R2) is 0.189. This shows that Product Quality (X1) and Price (X2) contribute 18.9 % of Buying Decisions (Y)